A new deep-sea scalpelliform barnacle, Vulcanolepas buckeridgei sp. nov. (Eolepadidae: Neolepadinae) from hydrothermal vents in the Lau Basin - Chan, Benny K.k.; Chang, Yen-Wei (Zootaxa, 2018)
The present study describes a new species of Vulcanolepas from the Lau Basin in the South Pacific. The basal angle of the tergum of Vulcanolepas buckeridgei sp. nov. is elevated from the capitular-peduncular margin at ~1/6 of the capitular height. The mandibles of V. buckeridgei sp. nov. are tridentoid; the cutting margins of the second and third teeth are long and each tooth possesses 18–20 sharp spines. The proximal segments of the anterior and posterior rami of cirrus I are protuberant and with dense, simple setae. DNA barcode sequences of Vulcanolepas buckeridgei sp. nov. are similar to Vulcanolepas sp. 1 collected from the Lau Basin (Herrera et al. 2015). Vulcanolepas buckeridgei is morphologically similar to Vulcanolepas ‘Lau A’ collected in the Lau Basin (Southward & Newman 1998). This suggests that Vulcanolepas buckeridgei sp. nov. is widespread in the Lau Basin.